Editorial Comments - Marie Poggenpoel; Annatjie Botes (AOSIS, 2000)
Assessment and evaluation of education,practice and research of health professionals are necessary in order to provide quality health services to our communities, country and internationally. In this edition most of the articles address assessment or evaluation of education practice or research. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.